Recent Advances in Microalgae Process for Post-combustion CO2 Capture - Gautam A.; Mondal M.K. (My University, 2025)
The world’s population has increased drastically in recent years, and various human activities have deteriorated the earth’s atmosphere. In this sequence, carbon dioxide (CO2) emission is a challenging problem in the current scenario, and every country is trying to eliminate this problem by implementing the concept of net-zero emissions. There are a few techniques available to capture CO2 from major industrial sectors: absorption, adsorption, chemical looping combustion, cryogenic separation, membrane separation, and microalgae process. Amongst all, the microalgae process is becoming very popular in recent years due to its large CO2 absorption capacity, high photosynthesis rate, economical and eco-friendly operation, etc. Microalgae are microscopic organisms that use photosynthesis in which CO2 is absorbed, and no special attention is required for their growth. It is well known that microalgae grow 100 times faster than terrestrial plants, and its end product is biomass that can be converted into valuable biofuel, i.e., bio-diesel and bio-ethanol. One of the most significant advantages of this process is that CO2 capture and biofuel production occur simultaneously. Therefore, the motivation of this study is mainly to target the basic concepts of the microalgae process used in CO2 capture, their recent advancements, their advantages and disadvantages, and their application. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.